PENGARUH PROFITABILITAS, LAGGED DIVIDEND, DAN INVESTMENT OPPORTUNITY SET TERHADAP KEBIJAKAN DIVIDEN - Hanifah Elka Yani; Novera Kristianti Maharani (GoAcademica Research dan Publishing, 2022)
The purpose of this study was to determine whether profitability, lagged dividend, and investment opportunity set affect dividend policy. The analysis in this study uses descriptive statistics, while hypothesis testing uses multiple linear regression, with the addition of a variable, namely the investment opportunity set as a gap theory from previous research which is still rarely studied. The results of this study indicate that there is a simultaneous influence between profitability, lagged dividend, and investment opportunity set on dividend policy. Partially, profitability and lagged dividend have a positive effect on dividend policy. While the Investment Opportunity Set partially negative effect on dividend policy. With the results of the coefficient of determination which shows that 43.8% of the dividend policy with the dimensions of the Dividend Payout Ratio (DPR) is influenced by the variables of Profitability, Lagged Dividend, and Investment Opportunity Set, the remaining 56.2% can be influenced by other variables.